Digest of Reports and Documents - Planning Commission (Planning Commission, 1980)
The key role of transport in development of the national economy has been undoubtedly recognised since the inception of the First Plan, but in determination of overall plan allocations it did not receive a matching priority with power or irrigation. In the face of financial constraints the approach to transport was generally towards creation of capacities mainly for moving specific categories of traffic for industrial projects and providing relief for passengers on congested urban networks. A comprehensive attempt to prepare a long-term transportation plan for the country as an integral part of the national macro-economic plan has still to be made.
The Report of the National Transport Committee
The Report of the National Transport Committee